(untitled) (ZOO-Journal, 2019)
Induced breeding is a scientific approach to the modern fish breeding procedure whereby ripen brood fishes are stimulated to release the eggs by pituitary hormone or any other synthetic hormone to breed in captive condition. Fish pituitary is mainly used for induced breeding but due to difficulties in the preparation of injections and preservation, nowdays synthetic hormones like LHRH-a, Ovaprim, WOVA-FH, Ovatide etc. are found to be used for induced breeding. A total of 4 sets of female grass carp were used for induced breeding with application of LHRH-a and pituitary extract in April at Mandal Fish Hatchery, Rupandehi. In total 23,67,500 eggs were collected and incubated. Fecundity, fertility and hatching rates were 1,25,000, 40-70% and 60-70% respectively. The rate of breeding especially, fertilization and hatching rate with LHRH-a was found better than with pituitary extracts.